Reliability and validity testing of an archery chronometer - Ertan, H.; Kentel, B. B.; Tümer, S. T.; Korkusuz, F. (Journal of Sports Science & Medicine, 2005)
Keeping the arrow velocity constant during consecutive shots and responding to "clicker's fall" are considered to be an important feature of archery performance. A specially designed device called an archery chronometer was developed to measure the reaction time of an archer to clicker's fall, arrow velocity, and external factors that may affect arrow velocity. The purposes of this study were to test (1) the validity of Clicker Reaction Time (CRT) measurer, and (2) the reliability of CRT in accordance with the Flying Time (FT)/Average Speed (AS), temperature (TEMP), wind speed (WS) and wind direction (WD) measurements. 20 elite archers participated in this study. The Reaction Time (RT), which was derived from EMG values and CRT from the archery chronometer were correlated to test the validity of the CRT measurer. The test re-test method was applied to test the reliability of archery chronometer. CRT scores were related with RT scores (r = .787, p < 0.01). The archery chronometer was valid in terms of predicting reaction time. The device was found to be reliable in measuring CRT, AS, FT, WS, WD, and TEMP. It was concluded that archery chronometer could be used for technical evaluation and enhancing ones shooting technique in archery.